Implementation of Green Human Resources Management (HRM) Practices in PT Unilever Tbk's 2024 Sustainability Report - Echa El Sabhet; Endah Kurniawati (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2026)
The article analyzes the application of Green Human Resource Management (GHRM) methods in the 2024 Sustainability Report of PT Unilever Indonesia Tbk. GHRM emphasizes incorporating environmental and social sustainability concepts into human resource policies to connect business strategy with the demands of multiple stakeholders. This research used a qualitative document analysis methodology to examine Unilever's initiatives in sustainable recruitment, staff training and development, performance management, well-being, and diversity and inclusion. The report indicates that Unilever has adopted inclusive recruitment and equitable employment practices, utilized the 70-20-10 learning model to cultivate future-ready, environmentally aware employees, and improved employee well-being through digital health applications. Fairness, diversity, and inclusion initiatives, such as gender parity and support for individuals with disabilities, enhance the company's social sustainability and embody the tenets of stakeholder theory, highlighting responsibility to both internal and external stakeholders. The study conceptually extends the GHRM framework by incorporating social and psychological well-being while offering guidance for firms seeking to integrate sustainability into human resource strategies. Unilever's experience illustrates that GHRM serves as both an environmental program and a strategic approach to achieving enduring sustainable value creation. However, the report primarily provides descriptive data; further primary research is needed to evaluate the direct impact of GHRM on employees’ green behaviors.